Calculation of the Copper Filling Factor of Electric Traction Drives including Graphical Representation - Riedel, Andreas; Roessert, Alexander; Kühl, Alexander; Franke, Jörg (2019 22nd International Conference on Electrical Machines and Systems, ICEMS 2019, 2019)
In order to achieve a higher power density of electric traction drives, one significant optimisation variable is the copper filling factor. A self-developed MATLAB program makes it possible to graphically display the filling factors known from the literature in order to visualize optimisation potentials. It is possible to display quadratic, rectangular as well as trapezoidal slot geometrics with round wires or flat conductors. The different wire diameters and their isolation can be chosen from IEC 60317-0-1 or can be inserted manually. After entering the required parameters, the slot geometry is fitted with round or flat conductors according to the principle of the orthocyclic winding scheme. By varying the slot geometry and the wire parameters, the optimum filling factor for different applications can be determined graphically and mathematically, taking into account the assembly air.
CRIS-Team Scopus Importer:2020-02-21
Keywords: electric traction drives; filling factors; MATLAB; optimisation; tool

Challenges and Solutions for Contacting Insulated Litz Wire Structures in the Context of Electromechanical Engineering - Seefried, Johannes; Riedel, Andreas; Kühl, Alexander; Franke, Jörg (Springer Nature, 2022)
The contacting process for insulated copper wires is one of the most challenging operations in the field of electromechanical engineering. New technologies used by electric motors and inductive charging devices increases the complexity of this process. A major factor contributing to increased process complexity is the use of litz wires which consist of numerous individually insulated thin wires. During the contacting process, each of the litz wires must be reliably stripped as well as electrically and mechanically connected to each other or additional contact elements. Therefore, the purpose of this publication is to show and evaluate various contacting processes that exhibit high potential for use with different types of litz wires. In each process evaluation, both shaped wires for electric motor applications and high-frequency litz wires for inductive charging applications are considered. The results are compiled in a process matrix which shows the contacting processes suitable for each wire type as well as their corresponding advantages and disadvantages.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Contacting technologies; Litz wire; Wireless power transfer

Challenges of the Hairpin Technology for Production Techniques - Riedel, Andreas; Masuch, Michael; Weigelt, Michael; Gläßel, Tobias; Kühl, Alexander; Reinstein, Sebastian; Franke, Jörg (2018 21st International Conference on Electrical Machines and Systems (ICEMS), 2018)
The electrification of the drive train of passenger cars is currently undergoing an evolution from windings previously drawn in, which are known from industrially used electrical machines, to windings specially tailored to the requirements of mobile electric traction. A main trend is the use of pluggable shape windings, so-called hairpins. In order to fully exploit the economic advantages of this winding, elaborated production concepts and strategies are required. Due to the novelty and the currently ongoing innovation of these type of windings, the differentiated manufacturing possibilities per process step have not yet been fully defined. In view of the economic efficiency, high process speeds with increasing process reliability play a major role. The aim of this paper is to show a process chain of hairpin technology that is as universally valid as possible, to name the different alternatives for each process step and to explain their characteristic
Keywords: Wires; Windings; Insulation; Manufacturing automation; Production systems; Conductors; Hairpin; Process Chain; Production Technologies

Comparison of Various Manufacturing Processes for Hairpin-Stators with Different Conductor Material - Riedel, Andreas; Kneidl, Maximilian; Seefried, Johannes; Kühl, Alexander; Franke, Jörg (Springer Nature, 2022)
The increasing demand for alternative drives in the mobility sector is continuously generating innovations in the development and production of electrical machines. The automotive industry relies more and more on traction machines with hairpin stators, as the process chain can be automated more easily and the copper filling factor can be increased. Enhancing the electrical copper filling factor in particular allows an improvement of the power density of the electrical machine. However, large conductor diameters lead to additional losses at high frequencies, as they occur in high-speed applications, due to eddy current effects. These operational disadvantages can be avoided by substituting the solid rectangular conductor by a litz-wire. Nevertheless, this semi-finished product requires a more complex manufacturing process. Within this paper the process chain for the production of a litz-wire hairpin-stator is illustrated and the challenges in the process chain of a stranded conductor compared to a solid conductor are presented. In this context, the manufacturing aspects for the production of the litz-wire hairpins are considered in detail.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Copper filling factor; Litz-wire; Process chain

Erkenntnisse aus der Biegesimulation von Flachdraht - Weigelt, Michael; Fröschl, Christian; Masuch, Michael; Riedel, Andreas; Franke, Jörg (Draht, 2018)
<span style="background-color: transparent; color: rgb(102, 102, 102); font-family: Georgia, "Times New Roman", serif; font-size: 14px; font-style: italic; font-variant-numeric: normal; font-variant-east-asian: normal; line-height: 20px;">Dank einer simultanen Entwicklung aus struktur-mechanischer FE-Simulation und Versuchserkenntnissen lassen sich Formspulen von Traktionsmotoren kosten- und zeiteffizienter gestalten und innerhalb eines definierten Prozessfensters fertigen.

Evaluation of different methods for removing the conductor insulation of stranded conductors - Riedel, Andreas; Hahn, Roman; Kühl, Alexander; Franke, Jörg (12th International Symposium on Advanced Topics in Electrical Engineering, ATEE 2021, 2021)
The ecological change in society and politics leads to an increased demand for alternative drives. In the field of mobility, this can be observed by ongoing innovations in research and development as well as in the production of electric machines. Currently, the automotive industry is focusing more and more on traction drives using hairpin technology. The reasons for this are the easier automation of the manufacturing process and the higher copper filling factors that can be achieved. The latter help to improve the power density. At high frequencies, which inevitably occur in high-speed applications, large conductor dimensions lead to additional losses due to eddy currents. To reduce these losses, twisted round wires can be used instead of flat conductors. Nevertheless, the manufacturing as well as the processing of this semi-finished product is more complex. The aim of this paper is to present and compare the possibilities for removing the required tape of the stranded conductor and to substantiate it with initial results. For this purpose, the general production chain of a hairpin stator is explained at the beginning of the paper in order to show the reasons why the removal of the bandage is of elementary importance. This is supplemented by technological aspects of stranded wire technology which cause-effect relationships serve as the basis for the main part of this paper.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Electric traction drives; Hairpin winding; Insulation material; Litz wire; Skinning methods; Stranded conductors

Evaluation of Machine Learning for Quality Monitoring of Laser Welding Using the Example of the Contacting of Hairpin Windings - Mayr, Andreas; Lutz, Benjamin; Weigelt, Michael; Gläßel, Tobias; Kißkalt, Dominik; Masuch, Michael; Riedel, Andreas; Franke, Jörg (8th International Electric Drives Production Conference (EDPC), 2018)

Experimental Investigation of a New Manufacturing Technology for Hairpin Stators with Litz Wires - Riedel, Andreas; Kühl, Alexander; Franke, Jörg; Graf, Rolf; Hubert, Thomas; Bauer, David (2022 12th International Electric Drives Production Conference, EDPC 2022 - Proceedings, 2022)
The increasing demand of electric drives in the mobility sector leads to continuous innovations in the development and production of electric machines. Currently, it can be seen that hairpin technology is well established in the automotive industry for traction drives. In addition to the high level of automation of the process, the reasons therefore are the achievable copper filling factors, which result from the flat conductors used and thus increase the power density of the electrical machine. However, at higher frequencies, as a result of higher driving speeds, large conductor dimensions, especially the height of the conductor, lead to undesirable aspects in the form of eddy current losses. These negative effects can be reduced by replacing the solid rectangular conductor with a stranded conductor. Therefore, the substitution of the conductor material in the field of hairpin technology can be classified as the next innovation stage. The base material is a twisted stranded conductor compacted into a rectangular shape. In this paper, a novel process chain for the manufacturing of a stranded hairpin stator is presented, individual process steps are analyzed and potential improvement measures are explained. Subsequently, an evaluation is made on the basis of an assembled and electrotechnically measured stator with stranded hairpins.
CRIS-Team Scopus Importer:2023-03-07
Keywords: electric traction drives; hairpin winding; litz-wire; stator manufacturing; stranded conductors; wire materials

Experimental Setup of a Process Chain for Contacting Litz Wires for Electrical Drives - Riedel, Andreas; Seefried, Johannes; Schmidt, Alexander; Kühl, Alexander; Franke, Jörg (30th International Conference on Electrical Contacts, ICEC 2020 - Proceedings, 2021)
The main objective in the development of electric drives is the continuous effort to increase the performance. One possibility to achieve this is the use of shaped litz wires. However, shaped litz wires present major challenges regarding the contacting process. In the preparation of the contacting process, the individual conductors of the litz wires must be completely stripped without residues and brought into a defined geometry. This preliminary process step is also known as compacting. The compacting process is the basis for the subsequent contacting of the litz wires with each other or with contact elements. One process for contacting the litz wires is laser beam welding. In the context of this publication, the process chain consisting of ultrasonic compacting and laser beam welding is evaluated. The focus is put on the possible variations of the litz wire topologies, which differ in single wire diameter, number of wires and degree of insulation. Depending on this, parameters for the two processes are elaborated. To evaluate the results, electrical and mechanical testing of the litz wire connections is carried out. In addition, different approaches for the qualification of the compaction quality, in particular the evaluation of insulation residues, are considered.
CRIS-Team Scopus Importer:2023-03-07

Implementation of the Needle Winding Technique for Diamond Coils - Bickel, Benjamin; Mahr, Alexander; Kühl, Alexander; Franke, Jörg; Meixner, Sebastian; Berendt, Emil; Riedel, Andreas (5th International Electric Drives Production Conference, 2015)

Influence of Enameled Wire Preparation on the Laser welding of Hairpin Windings - Gläßel, Tobias; Riedel, Andreas; Franke, Jörg; Kühl, Alexander (2022 IEEE 67TH HOLM CONFERENCE ON ELECTRICAL CONTACTS (HLM), 2022)
CRIS-Team WoS Importer:2023-02-10

Influencing Factors for the Ultrasonic Compacting Process of Insulated Litz Wires for Electric Drives - Seefried, Johannes; Riedel, Andreas; Lohbauer, Andreas; Baessler, Hendrik; Kühl, Alexander; Franke, Jörg (30th International Conference on Electrical Contacts, ICEC 2020 - Proceedings, 2021)
The increasing demand for new electric drive concepts in the automotive sector leads to innovations in the development and production of these drives. Due to the demand for steadily higher drive speeds, litz wires, also called stranded wires, offer various advantages in terms of loss reduction. These losses include current displacement due to the skin- and proximity effect in the wire at higher frequencies. However, these litz wires complicate the process step of contacting the winding ends. For example, during this contacting process it is necessary to connect a high number of individual wires electrically conductively and mechanically with each other. However, these individual wires must be stripped simultaneously during the process. One possibility to implement this process step is the ultrasonic compaction process. By applying and damping ultrasonic oscillations, the individual wires can be thermally stripped and also welded together. However, a wide range of influencing parameters must be validated for this process. These include relevant process parameters as well as properties of the litz wires used. Among other things, the properties can be divided into the type of insulation, the number of individual wires and their diameter. Within this publication, the essential process parameters are identified and evaluated in terms of the quality of the compaction by using suitable methods for measuring the node resistance.
CRIS-Team Scopus Importer:2023-03-07

Potentials of an Explicit Finite Element Analysis of the Bending Processes for Coated Copper Wires - Weigelt, Michael; Riedel, Andreas; Masuch, Michael; Mahr, Alexander; Gläßel, Tobias; Franke, Jörg (2017 7th International Electric Drives Production Conference (E|DPC), 2017)
The advancing electrification in industry and everyday life requires powerful electric drives providing highest efficiency. The winding as the core of these drives is subject to continuous development. Furthermore, it is of decisive importance to accelerate sample production for prototype construction and small series production of electric drives to shorten the innovation cycles. Coated bar-wound winding elements are increasingly important for the application in electric drives. The process window for damage free bending processes of coated copper wires is yet not defined. Structural mechanical finite element (FE) modelling is therefore a powerful tool to reduce costly trial-and-error loops and shortening development cycles for those production techniques as it provides reliable quantitative results. The aim of this paper is to propose the basics for defining a process window for the bending of flat wires using experimental bending test setups and FE-simulation tool
Keywords: finite element method; bending; flat wire

Process Reliable Laser Welding of Hairpin Windings for Automotive Traction Drives - Gläßel, Tobias; Seefried, Johannes; Masuch, Michael; Riedel, Andreas; Mayr, Andreas; Kühl, Alexander; Franke, Jörg (IEEE International Conference on Engineering, Science, and Industrial Applications (ICESI), 2019)
Keywords: Electric Drives Production; Hairpin Winding; Contacting Technologies

Robot-based Production of Electric Motors with Hairpin Winding Technolgy - Kühl, Alexander; Riedel, Andreas; Vogel, Alexander; Hartl, Sebastian; Gläßel, Tobias; Franke, Jörg (International Conference on Intelligent Automation and Robotics (ICIAR'19), 2019)

Towards an intelligent straightening system for flat enameled copper wire: problem statement, review of related work, and basic concept - Mayr, Andreas; Baader, Marcel; Raffin, Tim; Riedel, Andreas; Franke, Jörg (Procedia CIRP, 2022)
Enameled copper wire is a crucial material for the production of modern electrical machines. With the advent of hairpin windings, copper wire with rectangular cross-section is gaining importance. Being delivered on coil carriers, the wire is subject to initial curvatures which must be leveled out before further processing. Since common straightening systems are set manually and not controlled automatically due to missing sensor feedback, the straightening process is very susceptible to material-related deviations. After providing an in-depth problem statement, this paper gives a structured overview of related approaches and derives a basic concept for the intelligent straightening of flat enameled copper wire.<br